PEMBERDAYAAN PETERNAK MELALUI TEKNOLOGI SILASE UNTUK MENANGGULANGI KRISIS PAKAN DI MALANG - Andi Hasan; Nurul Humaidah; Umi Kalsum; Luthfi Awwalia (LPPI UMN AL WASHLIYAH, 2025)
The stable and sustainable livestock feed availability is one of the main challenges in the livestock sector, especially during the dry season. This condition affects the availability of forage for animal feed. This community service program, conducted by the Kandidat Magister Mengabdi (KMM) of the Animal Science Graduate Program at the Universitas Islam Malang (Unisma), aims to optimize silage production as an alternative feed reserve for farmers in the Malang area. The limited knowledge of alternative feed options among farmers prompted the implementation of this activity. The program was conducted through counselling, hands-on training, and mentoring on silage production using local materials such as elephant grass, corn, and agricultural waste. The high enthusiasm of farmers in participating in the counselling and practical sessions reflects their strong desire to survive during the dry season. The results of the activity indicate improved understanding and skills among farmers in processing and storing silage. Furthermore, there was an increased awareness of the importance of long-term feed management. This community service program makes a real contribution to strengthening food security and promoting the sustainability of small-scale livestock farming in the targeted area.